PROFIL VEGETASI HUTAN MANGROVE DI KAWASAN TELUK PANGPANG RESORT KUCUR TAMAN NASIONAL ALAS PURWO - Anam, Khoirul; Ardiyansyah, Fuad (Program Studi Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas PGRI Banyuwangi, Jalan Ikan Tongkol No 01, Telp (0333) 421593, 428592 Banyuwangi 68416, 2025)
Climate change and anthropogenic pressures threaten mangrove ecosystems, including in Pangpang Bay, Alas Purwo National Park. This study aims to analyze the mangrove vegetation profile in Kucur Resort, covering species diversity, density, zonation, and environmental parameters. The line transect plot method was applied across four stations (Mangrove Trail, Gendoh, Curah Wuluh, Pletesan), measuring vegetation structure (seedlings, saplings, trees), importance value index (IVI), and temperature, salinity, and pH. Results identified 11 true mangrove species from 7 families, dominated by Rhizophoraceae. Species such as Sonneratia alba, Rhizophora apiculata, and Ceriops tagal were widely distributed, while Bruguiera sexangula was only found in Gendoh. The highest density occurred in Mangrove Trail (2,554 trees/ha), with moderate Shannon-Wiener diversity (H'=1.57) and low evenness (E'=0.26–0.32). Classic zonation patterns were observed in three stations, driven by salinity and substrate gradients. These findings highlight the need for ecology-based conservation for sustainable management.